Xanthohumol ameliorates diabetic kidney disease through suppression of renal fibrosis by regulating SNHG10/miR-378b - Hao, Jian; Li, Hui; Yu, Weimin (Frontiers in Pharmacology, 2025)
ContentDiabetic kidney disease (DKD), commonly termed diabetic nephropathy (DN), is characterized by oxidative stress and renal tubular epithelial cells apoptosis driven by high glucose (HG).ObjectiveTo explore the protective effects and underlying mechanism of xanthohumol in DN mice and HG-induced HK-2 cells.Materials and methodsThe STZ-treated mice and HG stimulated HK-2 cells were applied to establish in vivo and in vitro DN models. The concentrations of blood glucose, serum creatinine, BUN and urine creatinine, and β-n-acetylglucosaminidase (NAG) activity was determined. The pathological changes of renal tissues were evaluated by Masson and periodic acid schiff (PAS) staining. TNF-α, IL-1β and IL-6 levels were detected using ELISA. Furthermore, CCK-8 assay and flow cytometer analysis were applied for determining HK-2 cells viability and apoptosis, respectively. Gene and protein levels was evaluated by qRT-PCR analysis and western blot/IHC. The relationship between lncRNA SNHG10 and miR-378b was confirmed by luciferase reporter assay.ResultsXanthohumol effectively improves DN-stimulated kidney structural and functional abnormalities. LncRNA SNHG10 was downregulated in the renal tissues of DN mice and HG induced HK-2 cells, while this inhibition was reversed by xanthohumol treatment. We also noted that xanthohumol remarkably reversed HG induced HK-2 cells injury. Upregulation of lncRNA SNHG10 also improved DN in mice. Meanwhile, downregulation of SNHG10 reversed the effects of xanthohumol on HG-induced HK-2 cells. Additionally, miR-378b directly targeted lncRNA SNHG10.Conclusion and discussionXanthohumol inhibited the progression of DN by regulating SNHG10/miR-378b, indicating a novel understanding of xanthohumol in DN progression and providing a latent therapeutic target for DN therapy.